The role of prosocial and proactive personality in customer citizenship behaviors. Issue 2 (13th March 2019) - Choi, Laee; Hwang, Jiyoung
Abstract : Purpose: This study aims to explore customer personality-related antecedents of customer citizenship behaviors (CCBs) that benefit service providers. It also investigates two-step consequences of CCBs: customer satisfaction and intention to continue the relationship. Design/methodology/approach: US consumers ( n = 665) participated in online surveys regarding three types of service businesses with different levels of customization and customer contact. Data were analyzed using structural equation modeling. Findings: Results show a significant, positive impact of the two dimensions of prosocial personality (i.e. other-oriented empathy and helpfulness) and proactive personality on CCBs. Additionally, CCBs increase customer satisfaction and, in turn, intention to continue the relationship. Research limitations/implications: This study suggests the importance of customer prosocial and proactive personality as antecedents of CCBs. Beyond intention to participate in CCBs, the present study shows that customers perceived satisfaction from CCBs, resulting in intention to continue the relationship with their service provider. Further research should investigate other types of customer personalities such as conscientiousness and agreeableness. Practical implications: Service providers should understand customer personalities that lead to voluntary behaviors that benefit their organizations. This understanding allows the service providers to better communicate with their customers and to receive more assists from customers. Originality/value: Previous research has shown that customers' attitudinal perceptions impact CCBs. In contrast, this study highlights the strong and positive impact of customer personalities, prosocial and proactive personality, on CCBs. Another significant contribution of this study is that it incorporates the potential consequences of CCBs.